1984
DOI: 10.1111/j.1365-2362.1984.tb00700.x
|View full text |Cite
|
Sign up to set email alerts
|

The renin‐angiotensin system during converting enzyme inhibition with captopril in patients with severe treatment‐resistant hypertension

Abstract: The effect of captopril on blood pressure (BP) and various components of the renin-angiotensin system was assessed in ten severely hypertensive patients. Captopril acutely reduced the BP with a maximum decrease of 23% at 90-120 min. Maintenance treatment with captopril alone could not control the BP in any of the patients. Addition of hydrochlorothiazide markedly reduced the BP, while supplementation with propranolol caused no consistent changes. Three patients attained a supine diastolic blood pressure (SDBP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…A similar experience has been reported in hypertensive and normotensive subjects (19). In agreement with our previous experience (20) and that of other investigators (2, 5), no correlations could be demonstrated between the long-term blood pressure reduction and pre-captopril PA11 levels. However, the thiazide-treated patients in group B had higher PA11 levels and a subsequent larger fall in blood pressure during captopril treatment than the untreated patients in group A.…”
Section: Discussionsupporting
confidence: 93%
“…A similar experience has been reported in hypertensive and normotensive subjects (19). In agreement with our previous experience (20) and that of other investigators (2, 5), no correlations could be demonstrated between the long-term blood pressure reduction and pre-captopril PA11 levels. However, the thiazide-treated patients in group B had higher PA11 levels and a subsequent larger fall in blood pressure during captopril treatment than the untreated patients in group A.…”
Section: Discussionsupporting
confidence: 93%
“…
Converting enzyme inhibition in mild and moderate essential hypertension. I. Acta Med Scand 1985; 218: 435-42.some authors to be proportional to the prevailing plasma concentrations of angiotensin I1 (4-7), whereas others have failed to find such a relationship (8,9). Maintenance therapy often leads to further reductions in blood pressure which in some studies have been shown to be correlated to the pretreatment levels of angiotensin I1 or renin (10-12), but not in others (7,9,(13)(14)(15).
…”
mentioning
confidence: 99%
“…I. Acta Med Scand 1985; 218: 435-42.some authors to be proportional to the prevailing plasma concentrations of angiotensin I1 (4-7), whereas others have failed to find such a relationship (8,9). Maintenance therapy often leads to further reductions in blood pressure which in some studies have been shown to be correlated to the pretreatment levels of angiotensin I1 or renin (10-12), but not in others (7,9,(13)(14)(15). The evidence for involvement of bradykinin in the hypotensive action Abbreviations: ACE = angiotensin converting enzyme, PRC = plasma concentration of renin, PRSC = plasma concentration of renin substrate, PA1 = plasma concentration of angiotensin I, PA11 = plasma concentration of angiotensin 11, BBK = blood concentration of bradykinin, DBP = diastolic blood pressure, MAP = mean arterial pressure, HR = heart rate.…”
mentioning
confidence: 99%